Cultural factors affecting persuasive design of smartphone applications to maintain customer loyalty - Faisal, Serri; Hamid, Nor Aziati Abdul; Abdullah, Nor Hazana (American Scientific Publishers, 2018)
Smartphone usage exhibits an asymptotic growth worldwide along with the increasing popularity of various smartphone applications. Against this backdrop, this research analyzes the effect of persuasive design on customer loyalty by perusing behavioral patterns of smartphone application users. Specifically, this study investigates the influence of cross-cultural dimensions towards users’ acceptance and loyalty by integration of persuasive technologies. Past studies reveal that cultural backgrounds affect adoption to computer applications as well as continued use of the applications. A matrix combining persuasive designs with cross-cultural influences is applied pragmatically to a widely used application across all ages and both genders. Economic statuses and educational backgrounds are discounted. This research intends to map the smartphone applications design with persuasive design principles.